2006
DOI: 10.1128/aem.72.5.3291-3301.2006
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Whole-Genome Amplification To Access Microbial Populations in Contaminated Sediments

Abstract: Low-biomass samples from nitrate and heavy metal contaminated soils yield DNA amounts that have limited use for direct, native analysis and screening. Multiple displacement amplification (MDA) using 29 DNA polymerase was used to amplify whole genomes from environmental, contaminated, subsurface sediments. By first amplifying the genomic DNA (gDNA), biodiversity analysis and gDNA library construction of microbes found in contaminated soils were made possible. The MDA method was validated by analyzing amplified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
142
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(147 citation statements)
references
References 54 publications
(70 reference statements)
5
142
0
Order By: Relevance
“…We also performed complementary analyses on the unamplified DNA to confirm and quantify the trends observed in the metagenomic libraries. Recent studies reported that MDA caused relatively little biases for the sequencing of single genomes (Pinard et al, 2006), but indicated that MDA caused biases in community composition when used on mixed communities (Abulencia et al, 2006;Bodelier et al, 2009). qPCR analyses indicated here that the bias in community composition introduced by MDA is quite strong.…”
Section: Experimental Biasesmentioning
confidence: 58%
“…We also performed complementary analyses on the unamplified DNA to confirm and quantify the trends observed in the metagenomic libraries. Recent studies reported that MDA caused relatively little biases for the sequencing of single genomes (Pinard et al, 2006), but indicated that MDA caused biases in community composition when used on mixed communities (Abulencia et al, 2006;Bodelier et al, 2009). qPCR analyses indicated here that the bias in community composition introduced by MDA is quite strong.…”
Section: Experimental Biasesmentioning
confidence: 58%
“…Small-insert metagenomic libraries generated from three MDA reactions shared a similar cluster of orthologous group profiles, indicating conservation of sequences by MDA. However, MDA from several microbes, experimentally mixed in known ratios, indicated that some bias may occur in their representation (Abulencia et al, 2006). In another subsurface study, Edwards et al (2006) demonstrated the first use of 454 pyrosequencing to characterize metagenomic DNA, employing MDA to obtain sufficient template using microbial assemblages from the Soudan Iron Mine in Minnesota, USA.…”
Section: Whole Community Genome Amplificationmentioning
confidence: 99%
“…Abulencia et al (2006) estimated that an untenable 11-88 kg of contaminated subsurface soil (at 10 4 cells g -1 ) would be necessary to extract microgram amounts of DNA for shotgun library construction, with 20-fold more required for BAC libraries. To overcome this, MDA was successfully applied to heavily contaminated subsurface-soil samples from Oak Ridge, Tennessee, to generate sufficient template for 16S rRNA gene PCR and construction of libraries.…”
Section: Whole Community Genome Amplificationmentioning
confidence: 99%
“…Ultimately, alternative methods that do not depend on the design and employment of oligonucleotide primers may reveal to what degree cloning and sequencing of PCR products gives a representative picture of microbial biodiversity in subsurface sediments. For example, strand displacement amplification of environmental DNA (reviewed in Hutchinson et al, 2005;Zhang et al, 2006) can generate sufficient amounts of DNA for further sequence analysis from DNA-limited sediment samples (Raghunathan, 2005;Abulencia et al, 2006). The method can be combined with highly efficient pyrosequencing of deep subsurface genomic DNA (Biddle, 2006).…”
Section: Implications: Have We Caught Them All?mentioning
confidence: 99%